Peningkatan Pemahaman dan Keterampilan Bisnis pada KATAR MARSEL melalui Pelatihan Business Model, Selling Skills, dan Literasi Keuangan - Carola Basuki; Anton Kurniawan; Lorio Purnomo (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
This Community Service Activities has the goal of assisting organizations in increasing knowledge and business development in their Human Resources through training in Business Model, Selling Skill, and Financial Literacy. Community Service Activities was carried out at Sudimara Selatan, Ciledug, Tangerang City. Karang Taruna Community (KATAR MARSEL) in South Sudimara was the target of Community Service Activities who have F&B business to sell coffee products. The problem faced by the community is that Human Resources lack knowledge about Business Model, techniques for selling products through a digital platform, and financial arrangements in the coffee business. The Community Service Activities team provided solutions to the community by providing training so that businesses engaged in selling coffee from the community's ideas can further develop by creating the right Business Model, selling products effectively through digital platforms, and managing finances efficiently. The methods used in this Community Service Activities were socialization methods, question and answer discussions, simulations, and review of community-owned coffee businesses. The results of this Community Service Activities that have been carried out are that the KATAR MARSEL Community has the knowledge and able to develop their business by made the right Business Model strategy, could optimize sales through the chosen social media platform and make accurate financial arrangements.